Quantifying declines in livestock due to land subdivision - Boone, Randall B.; BurnSilver, S.V.; Thornton, Philip K.; Worden, J.S.; Galvin, K.A. (2005)
In Kajiado District, Kenya, ranches held communally by Maasai are being subdivided into individually owned parcels. Livestock owners know that herds on parcels that are too small cannot be viable, but the decline in the capacity of parcels to support livestock has not been quantified. We used ecosystem modeling to represent the effects of subdivision as Maasai group ranches were divided into 196, 10, 5, 3, and 1 km2 parcels. Within the spatially explicit, process-based Savanna ecosystem model, we used maps that constrained the movements of livestock to be within parcels. We also modeled cooperative grazing associations, giving groups of herders access to parcels composed of dispersed or contiguous 1 km2 parcels. Vegetatively productive areas had higher carrying capacities when isolated because resident animals did not compete with animals moving in seasonally from other areas. In a ranch of low but heterogeneous productivity, we saw a steady decline in capacity under subdivision, until 25% fewer livestock could be supported on the ranch of 1 km2 parcels relative to the intact ranch. On a ranch with both low productivity and heterogeneity, 20% fewer livestock were supported when parcels were still 10 km2. The most productive ranch studied saw small population changes with subdivision. Participation in grazing associations was helpful in the ranch intermediate in productivity and heterogeneity, but not other ranches. Subdivision of Kajiado lands might be inevitable, but our results show the relative benefits to stakeholders if land owners and policy makers act to maintain open or flexible access to individually held parcels.